2011
DOI: 10.1108/20423891111179669
|View full text |Cite
|
Sign up to set email alerts
|

CETL for work based learning: enhancing innovation and creativity in teaching and learning

Abstract: Purpose -The purpose of this paper is to discuss three case studies reflecting areas of innovation and creativity which CETL funding made possible through a work-based learning CETL. CETL sponsored evaluations of funded projects and teaching initiatives informed further curriculum developments. Design/methodology/approach -Using a case study approach the paper explores the experiences of three different projects and the impact upon staff and students in a CETL for work-based learning. Three case studies are us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…The research findings during the past decade have generally supported the notion that workbased learning activities can invigorate the learning process and act as a positive force for students in academic, vocational, and technical education programs (Swail and Kampits, 2004). Workman et al (2011) showed in their study that work-based learning is effective in enhancing innovation and creativity in teaching and learning. Community-based, problem-based learning, and service learning are also learning approaches that can enhance students' creativity and innovatory competences in real-life situations (Dailey-Hebert and Donnelli, 2010;Hardwick, 2013).…”
mentioning
confidence: 99%
“…The research findings during the past decade have generally supported the notion that workbased learning activities can invigorate the learning process and act as a positive force for students in academic, vocational, and technical education programs (Swail and Kampits, 2004). Workman et al (2011) showed in their study that work-based learning is effective in enhancing innovation and creativity in teaching and learning. Community-based, problem-based learning, and service learning are also learning approaches that can enhance students' creativity and innovatory competences in real-life situations (Dailey-Hebert and Donnelli, 2010;Hardwick, 2013).…”
mentioning
confidence: 99%
“…El uso de tecnologías como recurso para mejorar la enseñanza y el aprendizaje ha dado buenos resultados en títulos de educación superior, y mejora la comprensión epistemológica del futuro alumno que se va a incorporar al ámbito profesional (Workman, 2011), resultando un claro objetivo de las competencias transversales. En este sentido, el grupo de innovación docente (EICE), «Recursos Tecnológicos para el aprendizaje jurídico, la documentación y comunicación audiovisual (RETAJUDOCA)», cuyo objetivo principal es utilizar recursos tecnológicos para el aprendizaje privilegiando la aplicación de las nuevas tecnologías de la información y comunicación (TICs), ha desarrollado una producción propia de casos prácticos jurídicos basados en películas, series y documentales (Ramón et al, 2016(Ramón et al, , 2017(Ramón et al, , 2018(Ramón et al, , 2019(Ramón et al, , 2021.…”
Section: Introductionunclassified
“…Several evaluations of learning outcomes of a workbased training and the significance of managerial support have been covered in the research of Swedish researchers Eva Ellström and Per -Erik Ellström who have reasonable and proved findings on the importance of management support for effective realisation of work-based training programme (Ellström & Ellström, 2014). The work-based training has different influencing aspects regarding country and training level (Orr, & Simmons, 2011), as well as participation rates (Thomas & Qiu, 2012), different research methods applied to find better solutions, like insider researcher (Workman, 2007), enhancing innovation and creativity in teaching (Workman, et al, 2011). Employers often face also such employee problems as productivity, issues of morale, poor performance and other problems (Plump, 2010).…”
Section: Theoretical Backgroundmentioning
confidence: 99%